Person-centred care for dementia patients (front end system development) - Ang, Royce Jia Jie (Nanyang Technological University, 2022)
Dementia is a progressive neurodegenerative brain disease defined as irreversible functional and cognitive impairment. The prevalence of dementia is expected to rise and is not just a medical problem but an enormous socioeconomic burden for the individual, family, and the country. Thus, the Person-centred care approach is adopted in care centres to ensure good dementia care. Person-centred care is contingent upon knowing the individual via an interpersonal relationship and focuses on building around the needs of the individual. However, with an uncompromising chronic demand for attachment from patients with dementia (PWD), caregivers are susceptible to caregiving strain.